Design of A Pepper Washing Machine From A Modified 2-Tube Washing Machine - Basir, Al Qadri; Sukainah, Andi; Akram Mukhlis, Andi Muhammad (Agricultural Technology Education Study Program, 2024)
This research aims to modify a 2-tube washing machine into a pepper washing machine. You can find out the percentage of peeled and unpeeled seeds as well as the capacity of the tool. The form of research used is research and development (R&D), which aims to develop or modify an existing product. The data analysis technique used in this research is quantitative data analysis technique. The research results concluded that the capacity and percentage level of success of the tool had a capacity of 7 kg in 11.5 minutes or 0.61 kg in 1 minute, with a percentage of peeled pepper seeds of 98.22 percent and pepper seeds not peeled of 1.78 percent. Based on the conclusions of the research results, it is recommended: Make modifications to the net, so that when washing pepper it does not enter between the net gap and the washing tub. Study of the loading system to make it easier to put pepper into the washing tub and unloading so that the seeds can easily come out of the washing tub. Carry out a washing test on a larger cycle.